PENGARUH MODEL REASONING TERHADAP KEBERANIAN SISWA DALAM BERPENDAPAT DAN MENGAMBIL KEPUTUSAN PADA MATA PELAJARAN PPKN DI MTS SEHATI ULUTEDONG KABUPATEN BULUKUMBA - Andi Ashabul Kahfi; Muhajir; Rismawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the influence of the reasoning learning model on students’ courage to express opinions and make decisions in the Civics (PPKn) subject. The background of this research is based on the low level of students' confidence in expressing opinions and making decisions, which are essential not only in the learning process but also in their social lives.This research uses a quantitative approach with a quasi-experimental design. The population consists of all eighth-grade students at MTs Sehati Ulutedong, totaling 49 students from two classes. Class VIII A (25 students) served as the experimental class and was treated using the reasoning model, while Class VIII B (24 students) served as the control class, using conventional learning methods. The sampling technique applied was purposive sampling. Data were collected using questionnaires, observations, and documentation, which were used to assess and support students’ involvement in critical thinking and decision-making processes. Data were analyzed using an independent sample t-test. The results showed a significant influence of the reasoning model on students’ courage, as indicated by a t-value of 7.514and a significance level of 0.000, meaning there is a statistically significant difference between the experimental and control groups.In conclusion, the reasoning model is effective in enhancing students’ courage to express opinions and make logical and responsible decisions. The model improves not only cognitive aspects but also affective aspects, such as self-confidence and critical thinking abilities.